2013
DOI: 10.1177/2051415813488367
|View full text |Cite
|
Sign up to set email alerts
|

Minimising the risk of device infection in penile prosthetic surgery: a UK perspective

Abstract: We have reviewed articles published on penile prosthetic infection in Medline and EMBASE databases from 2000 to 2012 with the intention of signposting ‘best evidence’ for the UK prosthetic implanter. Using the Oxford Centre for Evidence-based Medicine Levels of Evidence (LE), no paper exceeded an LE of 2b and the majority were LE 4 (case series) and LE 5 (expert opinion). This is not surprising from a UK perspective since HES data for 2009 to 2010 reported 263 penile prosthetic surgeries performed in 35 hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Recent studies have found the rate of postoperative infection following IPP implantation to be between 0.5% and 3%. 6 , 7 , 8 , 9 , 10 , 11 , 12 However, many of these recent studies exclude at-risk demographics, such as those with a history of prior IPP implantation, 3 , 6 , 7 , 9 , 20 IPP infection, 5 , 10 , 11 , 14 and successive revisions. 5 , 8 After including these at-risk demographics, our study determined the rate of postoperative infection to be 8.20%, a rate higher than that quoted in recent studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have found the rate of postoperative infection following IPP implantation to be between 0.5% and 3%. 6 , 7 , 8 , 9 , 10 , 11 , 12 However, many of these recent studies exclude at-risk demographics, such as those with a history of prior IPP implantation, 3 , 6 , 7 , 9 , 20 IPP infection, 5 , 10 , 11 , 14 and successive revisions. 5 , 8 After including these at-risk demographics, our study determined the rate of postoperative infection to be 8.20%, a rate higher than that quoted in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have provided varied evidence regarding the rate of postoperative complications for those undergoing IPP revision. While all but 1 study reviewed 16 revealed that those undergoing revision experienced greater rates of complications, 5 , 8 , 12 the reported complication rates for these patients have varied. While some studies quote the infection rate for these patients to be as high as 10–18%, 5 , 8 , 12 , 14 other studies report that, with proper device washout and the use of other infection limiting techniques, 16 this rate may be as low as 3–4%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations